2020
DOI: 10.1111/acel.13289
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation suppresses JNK3 by activation of ERK/MKP7 to attenuate AMPA receptor endocytosis in Alzheimer's disease

Abstract: Alzheimer's disease (AD), a severe age‐related neurodegenerative disorder, lacks effective therapeutic methods at present. Physical approaches such as gamma frequency light flicker that can effectively reduce amyloid load have been reported recently. Our previous research showed that a physical method named photobiomodulation (PBM) therapy rescues Aβ‐induced dendritic atrophy in vitro. However, it remains to be further investigated the mechanism by which PBM affects AD‐related multiple pathological features to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 60 publications
(76 reference statements)
0
37
0
Order By: Relevance
“…Western blot analysis and co‐immunoprecipitation (co‐IP) were performed following previous description with some modification (Bourdenx et al, 2021; Shen et al, 2021; Zhang et al, 2021). We performed plasma membrane protein isolation according to the directions provided by Minute™ Plasma Membrane Protein Isolation and Cell Fractionation Kit (Invent Biotechnologies, catalog number: SM‐005).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis and co‐immunoprecipitation (co‐IP) were performed following previous description with some modification (Bourdenx et al, 2021; Shen et al, 2021; Zhang et al, 2021). We performed plasma membrane protein isolation according to the directions provided by Minute™ Plasma Membrane Protein Isolation and Cell Fractionation Kit (Invent Biotechnologies, catalog number: SM‐005).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, reduced function of CaMKII, a fundamental signaling protein in LTP, is also implicated (Gu et al, 2009; see also Ghosh & Giese, 2015). Although the mechanisms responsible for the decline in AMPAR number and surface expression are varied and complex, it is likely that an impairment in intracellular endocytic recycling and increased AMPAR endocytosis at synaptic sites has a critical role (Shen et al, 2021; Xian et al, 2018; Zhao et al, 2010). Other evidence suggests that increased internalization of AMPARs stimulated by Aβ accumulation is due to enhanced ubiquitination of receptors followed by their degradation (Guntupalli et al, 2017; Rodrigues et al, 2016; Zhang, Guo, et al, 2018).…”
Section: Synaptic Ampar Trafficking Is Targeted In Neurodegenerative ...mentioning
confidence: 99%
“…The study revealed potential therapeutic value by achieving regulation of the JNK3 kinase pathway and stabilizing the MKP7 cascade, which is believed to be brain-specific isoforms associated with neurodegeneration cascades. Observed molecular changes translated into the rescue of memory loss deficit, amyloid load reduction, synaptic loss, and neuroinflammation in AD model transgenic APP/PS1 mice treated with PBM ( Shen et al, 2021 ). The beneficial findings observed in AD model animal studies draw more attention and build an evidence-based foundation in the biomedical community to make more clinical trials.…”
Section: Effects Of Transcranial Near-infrared Light Stimulations In ...mentioning
confidence: 99%